Impacts of urea and 3,4-dimethylpyrazole phosphate on nitrification, targeted ammonia oxidizers, non-targeted nitrite oxidizers, and bacteria in two contrasting soils - Wang, Qing; Zhao, Ziting; Yuan, Manyao; Zhang, Zhijun; Chen, Shanshuai; Ruan, Yunze; Huang, Qiong (Frontiers in Microbiology, 2022)
This study explored the effects of combined urea and 3,4-dimethylpyrazole phosphate (DMPP) on several components critical to the soil system: net nitrification rates; communities of targeted ammonia oxidizers (ammonia-oxidizing archaea (AOA) and bacteria (AOB) and complete ammonia-oxidizing bacteria (comammox)); non-targeted nitrite-oxidizing bacteria (NOB) and bacteria. We conducted the study in two contrasting soils (acidic and neutral) over the course of 28 days. Our results indicated that DMPP had higher inhibitory efficacy in the acidic soil (30.7%) compared to the neutral soil (12.1%). The abundance of AOB and Nitrospira-like NOB were significantly positively associated with nitrate content in acidic soil. In neutral soil, these communities were joined by the abundance of AOA and Nitrobacter-like NOB in being significantly positively associated with nitrate content. By blocking the growth of AOB in acidic soil—and the growth of both AOB and comammox in neutral soil—DMPP supported higher rates of AOA growth. Amplicon sequencing of the 16S rRNA gene revealed that urea and urea + DMPP treatments significantly increased the diversity indices of bacteria, including Chao 1, ACE, Shannon, and Simpson in the acidic soil but did not do so in the neutral soil. However, both urea and urea + DMPP treatments obviously altered the community structure of bacteria in both soils relative to the control treatment. This experiment comprehensively analyzed the effects of urea and nitrification inhibitor on functional guilds involved in the nitrification process and non-targeted bacteria, not just focus on targeted ammonia oxidizers.